Single–spin asymmetries in electron–proton and photon-proton scattering in the Bethe–Heitler processes induced by loop corrections - Afanasev, A.V.; Konchatnij, M.I.; Merenkov, N.P. (Вопросы атомной науки и техники, 2007)
The single–spin target asymmetries in the hard electroproduction process e⁻ + p → e⁻ + γ + p and in the e⁺e⁻-pair photoproduction γ + p → e⁺ + e⁻ + p, induced by the loop radiative corrections to the vertex part of lepton interaction are considered. The physical reason to appearance such a kind of asymmetries is the nonzero imaginary part of the respective Bethe-Heitler amplitudes (on the level of radiative correction). The single–spin target asym-metries at unpolarized ingoing electron or photon beams and at arbitrary polarizations of the target proton for condi-tions of CLAS (Jefferson Lab, USA) and HERMES (DESY) experiments are calculated. Досліджені односпінові асиметрії мішені в процесах “жорсткого” електронародження e⁻ + p → e⁻ + γ + p і в фотонародженні e⁺e⁻--пар γ + p → e⁺ + e⁻ + p, індуковані петлевими радіаційними поправками в лептон-ній частині взаємодії. Фізичною причиною, що обумовлює такого виду асиметрії, є ненульова уявна частина Бете-Гайтлерівської амплітуди, яка з’являється на рівні радіаційної поправки. Односпінові асиметрії мішені у випадку неполяризованого електронного (чи фотонного) пучків та довільної поляризації протона-мішені обчислені в кінематичних умовах експериментів по електронародженню CLAS (Jefferson Lab, USA) і HERMES (DESY). Исследованы односпиновые асимметрии мишени в процессах “жесткого” электророждения e⁻ + p → e⁻ + γ + p и в фоторождении e⁺e⁻--пар γ + p → e⁺ + e⁻ + p, индуцированные петлевыми радиационными поправками в лептонной части взаимодействия. Физической причиной, обуславливающей такого вида асимметрии, является ненулевая мнимая часть Бете-Гайтлеровской амплитуды, которая появляется на уровне радиационной поправки. Односпиновые асимметрии мишени в случае неполяризованного электронного (или фотонного) пучка и произвольной поляризации протона-мишени вычислены в кинематических условиях экспериментов по электророждению CLAS (Jefferson Lab, USA) и HERMES (DESY).